"History of a dictatorship": an unfinished political essay by the young Fernando Pessoa - Barreto, José (2015)
The first part of this article reviews the materials from Pessoa's literary remains associated with the book project from 1909 to 1910 titled "History of a Dictatorship." These materials remain little known and mostly unpublished.The second part examines some centralthemes and theses of this unfinished politicalwork and places them within the evolution of Pessoa's thought'.